PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Halim, Jenny Puspita; Lindrawati, Lindrawati; Wardani, Rr. Puruwita (Widya Mandala Surabaya Catholic University, 2014)
In managing its operating activities, company are not only oriented toward profit but it also needs to be committed to be ethic, operate legally and contribute to increase the quality of its employee’s life, local communities, and the wider community. The company would made the disclosure to obtain recognition of certain parties and it can be through Corporate Social Responsibility Disclosure (CSR) which is disclose in annual report. The company that have good CSR disclosure will be responded positively by investors through in-creased share price. They are also supported by institusional ownership, it would be better. Therefore, this studyaim to examine insti-tusional ownership as a moderating variable between CSR disclosure to firm value. The research design using a quantitive approach to test hypotesis of the influance of CSR disclosure to firm value with institusional ownership as a moderating variable. This study’s object is the companies which is listed on Indonesian Stock Exchange from 2010-2012. The data collecting method is using documentation method. Data analysis technique is multiple regression analysis using Moderated Regression Analysis (MRA). The result of this study show a significant positive effect for CSR disclosure to firm value. Meanwhile, institusional asmoderating variable was unable strengthen CSR disclosure to firm value.